Gluten Intake and All-Cause and Cause-Specific Mortality: Prospective Findings from the UK Biobank. Issue 3 (31st December 2020) - Behrendt, Inken; Fasshauer, Mathias; Eichner, Gerrit
ABSTRACT: Background: Gluten has been linked to adverse effects on metabolic and vascular health. Objectives: The present study determines the association between dietary gluten intake and all-cause (primary objective), as well as cause-specific, mortality in people without celiac disease. Methods: Gluten intake was estimated in 159, 265 participants of the UK Biobank which is a large multicenter, prospective cohort study initiated in 2006. Cox proportional hazard regression models were used and HRs were determined for all-cause and cause-specific mortality. All models were adjusted for confounders and multiple testing. Results: Median (IQR) age was 57 (49–62) y with 52.1% of participants being female. Gluten intake was 8.5 (5.1–12.4) g/d with significantly higher consumption in males [10.0 (6.3–14.1) g/d] than in females [7.2 (4.6–10.7) g/d] ( P < 0.0001). During a median follow-up of 11.1 (10.6–11.9) y and 1.8 million person-years, 6259 deaths occurred. Gluten intake was not significantly associated with all-cause mortality after adjusting for confounders (HR: 1.00; 95% CI: 1.00, 1.01; P = 0.59). Dietary gluten was not significantly associated with cancer (HR: 1.00; 95% CI: 1.00, 1.01; raw P = 0.24) or noncancer (HR: 1.00; 95% CI: 0.99, 1.01; raw P = 0.56) mortality. However, gluten intake was positively associated with ischemic heart disease mortality (HR: 1.02; 95% CI: 1.01, 1.04; raw P = 0.003, Holm-adjusted P = 0.04). Conclusions: Gluten intake is not significantly associated with all-cause and cancer mortality in adults without celiac disease. The findings support the hypothesis that limiting gluten intake is unlikely to provide significant overall survival benefits on a population level. The positive association between gluten intake and ischemic heart disease mortality requires further study.